PENGARUH PENERAPAN MODEL DIRECT INSTRUCTION BERBANTUAN MIND MAPPING TENTANG BESARAN, SATUAN DAN PENGUKURAN DI MTS ISLAMIYAH PONTIANAK - Sinambela, Jepri P; Djudin, Tomo; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractAbstract: The aim of this study was to determine the effect of the implementation of direct instruction using mind mapping to enhance the students’ outcomes in quantities, unit and measurement to the seventh grade students of Mts Islamiyah Pontianak. The research was conducted in form of pre-experimental design with one group pretest-posttest design. The sample was chosen by using intact group method, the seventh grade with the number of 19 students to be treated. Based on result from t-test, the significant value was 0,00 that is smaller than 0,05, So it was concluded that h0 was rejected and ha was accepted, which means the implementation of direct instruction using mind mapping influence and increase students’ outcomes. The effect size after the treatment based on the calculation of n-gain was 0,25 with low category. This data showed that there was difference of learning outcomes before and after the treatment. This research is expected to be one of the teaching alternatives for teacher to improve students’ outcomes. Keywords: Direct Instruction, Mind Mapping, Student’s Outcome